Search for vector-like-fermion in the CMS detector at the LHC : one low transverse momentum muon and missing transverse momentum final state (2022)
ABSTRACT: Dark matter (DM) is a key concept to deeply understand the cosmological architecture of the universe, its existence is well accepted inside the physics and astrophysical community since the evidence supporting this interpretation is overwhelming. The standard model of particle physics (SM) is a theoretical framework that explains fundamental particles characteristics and how they interact among them. Despite its success the SM is not able to produce a candidate that has the proven properties of DM if it exists, finding DM is a challenging task, since its properties make its detection extremely complicated. Collider searches as well as the direct and indirect detection tests have produced negative results in terms of DM candidates but have resulted in limiting the parameter space of many models or ruling them out altogether. There are hypotheses and models proposed to explain DM physical nature. We focus on a model simple enough to be able to perform a realistic estimation of signals and backgrounds, but which can include DM. Using physically motivated selection of events upon the signals and backgrounds samples generated using a set of computational tools, we present the possible regions which could be explored to find the DM candidate, using the compact muon solenoid (CMS) setup as the likely experiment to perform this search in the LHC.